Respiratory Mechanics - Wilson, Theodore A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book thoroughly covers each subfield of respiratory mechanics: pulmonary mechanics, the respiratory pump, and flow. It presents the current understanding of the field and serves as a guide to the scientific literature from the golden age of respiratory mechanics, 1960 - 2010. Specific topics covered include the contributions of surface tension and tissue forces to lung recoil, the gravitational deformation of the lung, and the interdependence forces that act on pulmonary airways and blood vessels. The geometry and kinematics of the ribs is also covered in detail, as well as the respiratory action of the external and internal intercostal muscles, the mechanics of the diaphragm, and the quantitative compartmental models of the chest wall is also described. Additionally, flow in the airways is covered thoroughly, including the wave-speed and viscous expiratory flow-limiting mechanisms; convection, diffusion and the stationary front; and the distribution of ventilation. This is an ideal book for respiratory physiologists, pneumologists, exercise physiologists, and critical care physicians. This book also: Maximizes reader insights into current and landmark respiratory mechanics research Concisely yet thoroughly explores the current research on pulmonary mechanics, the respiratory pump, and flow Serves as an invaluable guide for those entering the field, or those seeking to expand their knowledge of it.
Lung mechanics -- The chest wall and the respiratory pump -- Flow and gas transport. .
Keywords: Regenerative medicine; Respiratory organs -- Diseases; Biomedical engineering; Regenerative Medicine and Tissue Engineering; Pneumology; Biomedical Engineering and Bioengineering